2015
DOI: 10.1039/c5ra14867g
|View full text |Cite
|
Sign up to set email alerts
|

Development of antibacterial polyacrylonitrile membrane modified with a covalently immobilized lysozyme

Abstract: : A novel antibacterial polyacrylonitrile (PAN) membrane covalently 3 immobilized with lysozyme was prepared. First, the virginal PAN membranes were 4 prepared via the classic immersion precipitation method. After modification with 5 NaOH, HCl, Ethylenediamine (EDA), lysozyme was covalently immobilized onto the 6 surface of PAN membranes by glutaraldehyde. The chemical compositions of virginal 7 and modified membranes were characterized by Fourier Transform Infrared 8 spectroscopy (FT-IR) and Energy Dispersion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The catalytic role of lysozyme is well documented in the literature, both in solution and in the crystalline state . The effect of HEWL in solution and in crystalline form at the interface with HCMs on a culture of Micrococcus lysodeikticus is shown in Figure as decrease in optical density (OD450).…”
Section: Resultsmentioning
confidence: 89%
“…The catalytic role of lysozyme is well documented in the literature, both in solution and in the crystalline state . The effect of HEWL in solution and in crystalline form at the interface with HCMs on a culture of Micrococcus lysodeikticus is shown in Figure as decrease in optical density (OD450).…”
Section: Resultsmentioning
confidence: 89%
“…They concluded that the presence of nanopatterns minimized the deposition of colloidal foulant, increased the permeation, and reduced the cake formation. [239] They obtained excellent antibacterial properties with S. aureus. Higher angles reduced the colloidal fouling in these UF membranes.…”
Section: Recent Trends In Surface Modification Strategiesmentioning
confidence: 98%
“…Liu et al immobilized lysozymes on PAN membrane surfaces using NaOH, ethylenediamine, and glutaraldehyde. [239] They obtained excellent antibacterial properties with S. aureus. Cegielska-Radziejewska et al modified UF membranes with lysozymes extracted from chicken egg white.…”
Section: Wwwadvsustainsyscommentioning
confidence: 98%
“…Nowadays, an immobilized form of lysozyme is regularly used by the food packaging and pharmaceutical industries to increase the antibacterial surface area (Cordeiro & Werner, ). For example, lysozyme immobilized with microbial chitosan (Cappannella et al., ; Lian, Ma, Wei, & Liu, ), polyacrylonitrile (PAN) (Liu et al., ), mesoporous silica nanoparticle (MSN) (Kao, Lin, & Mou, ), and cellulose (Edwards, Prevost, Condon, French, & Wu, ) were more effective against Oenococcus oeni , E. coli O157: H7, S. aureus , and Micrococcus lysodeikticus than the native enzyme. This strategy represents a new milestone in working towards food safety and safe pharmaceuticals.…”
Section: Exopolysaccharide‐degrading Enzymesmentioning
confidence: 99%